Pelatihan Pengembangan Rubrik Evaluasi untuk Guru SD di Kota Surabaya - Andhega Wijaya; Faridha Nurhayati; Abdul Rachman Syam Tuasikal; Mochamad Ridwan; M. E. Winarno; Nurrul Riyad Fadhli; Taufik Taufik; Dwi Lorry Juniarisca; Dona Sandy Yudasmara (Universitas Negeri Surabaya, 2025)
Physical Education, Sports, and Health (PJOK) plays a crucial role in realizing the educational role and improving students' physical fitness, motor skills, knowledge, healthy and active lifestyles, sportsmanship, and emotional intelligence. However, teacher professionalism is not yet optimal and still requires guidance and direction to achieve learning programs. Furthermore, PJOK teachers are unable to meet or are categorized as not meeting the basic competency requirements in the curriculum. Therefore, the community service team's targeted solution to address the challenges faced by PJOK teachers is to provide training on developing evaluation rubrics. This resulted in an evaluation rubric for the knowledge and skills components. Each basic competency is described, and each component contains several indicators included in the evaluation rubric. The methods used in this community service include lectures, discussions, practice, outcome measurement, and follow-up. The partner in this community service is the Surabaya Community Service Group (KKG). The product of this activity is a completed evaluation rubric that can be applied by teachers based on their needs and implemented in PJOK learning. Meanwhile, the outputs of this community service activity include ISSN journal articles, mass media publications, intellectual property rights, and community service products.